Características sociodemográficas, de saúde e de cuidados que influenciam a qualidade do sono de idosos cuidadores de idosos - Santos, Kelly Cristina dos (Universidade Federal de São Carlos, 2021)
Background: poor sleep quality can be considered an important public health problem, due to its high prevalence among older adults and the negative effects on affected individuals’ well being. When it comes to older adults caring for other older adults, poor sleep quality can compromise the care provided, especially in contexts of high social vulnerability. Thus, through the early identification of this condition and its related factors, interventions can be planned in order to reduce spending on health services and improve the quality of life of these individuals. Objective: to analyze the sociodemographic, health and context-related characteristics of care according to the quality of sleep of older adults who care for older adults. Method: an observational, cross-sectional and quantitative study, carried out with 65 old caregivers, in the coverage area of five Family Health Units in a context of high social vulnerability in the city of São Carlos, SP. Data were collected at participants’ homes through the application of questionnaires for sociodemographic, health and care context characterization, sleep quality assessment, depressive symptoms screening, functional capacity assessment for Basic and Instrumental Activities of Daily Living. Fisher’s Exact and Pearson’s χ2 were used. A significance level of 5% was adopted. Results: old female caregivers predominated, aged 60 to 74 years, with low education and insufficient income, with multimorbidity, without depressive symptoms, independent for basic activities and partially dependent for Instrumental Activities of Daily Living. They took care of their spouses, did not have training or help from other people to take care of them. Approximately 74% of them had poor sleep. There was a statistically significant relationship between sleep quality and sex (p=0.002), functional capacity for Basic Activities of Daily Living (p=0.003) and daily time spent in care (p=0.024). Conclusion: old female caregivers, who are dependent on basic activities of daily living and who perform the task of caring for more than 12 hours, are a major source of poor sleep and sleep disorders.
Sociodemographic, health and care characteristics that influences the sleep quality of older caregivers of older adults
Keywords: Idoso; Cuidadores; Sono; Vulnerabilidade social; Saúde da família; Enfermagem geriátrica; Aged; Caregivers; Sleep; Social vulnerability; Family health; Geriatric nursing; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA